Corporate social responsibility : reconciling aspiration with application - Kakabadse, Andrew; Morsing, Mette (Palgrave Macmillan, 2006)
This unique collection of international papers integrates CSR theory, research and practice. The book examines the challenges of regulating and reporting CSR application, exploring issues concerning all agencies involved. Recommendations for performance enhancement are complimented by insightful enterprise and case studies on CSR sustainability.